2015
DOI: 10.1155/2015/580474
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in Diabetes and Cardiovascular Disease: An Updated Review of the Literature

Abstract: The dietary reference values for Vitamin D were set primarily considering its role in bone health, but with the discovery of Vitamin D receptors throughout body tissues, new links with other health conditions are now studied, such as for diabetes and cardiovascular diseases (CVD). This paper shall analyze and examine all new research studies carried out, especially in 2013–2015 regarding diabetes mellitus (DM) and cardiovascular diseases (CVD). Vast research has been carried out to establish strong relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 118 publications
(125 reference statements)
0
44
0
1
Order By: Relevance
“…Low levels of serum vitamin D may also contribute to insulin secretion through its direct effect on the β-cell function [35]. Moreover, vitamin D deficiency could be an indirect risk factor for CHD as it may produce serious consequences such as immunosuppressive effect and inflammatory markers [36].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of serum vitamin D may also contribute to insulin secretion through its direct effect on the β-cell function [35]. Moreover, vitamin D deficiency could be an indirect risk factor for CHD as it may produce serious consequences such as immunosuppressive effect and inflammatory markers [36].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 TPEF, on the other hand, occurs when two incident infrared photons promote a molecule to its excited state in lieu of a single visible or ultraviolet photon. 4,5 Because TPEF also uses pulsed infrared light, it can be performed simultaneously with CARS in a multimodal microscope. Both tools are well matched for visualizing sweat dynamics, as these methods enable the rapid acquisition of images based on the concentration of specific chemical species without the need for tissue fixation, processing, or exogenous labels.…”
Section: Sweating the Small Stuffmentioning
confidence: 99%
“…Additionally, studies have found that vitamin D is markedly beneficial to the cardiovascular 16 , immune and respiratory systems 17,18 . Even though the significance of vitamin D and its involvement in bone metabolism have been well documented [19][20][21][22][23][24][25][26][27][28][29][30][31] , limited studies have been conducted on the effects of osseointegration of implants in dental patients.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the significance of vitamin D and its involvement in bone metabolism have been well documented [19][20][21][22][23][24][25][26][27][28][29][30][31] , limited studies have been conducted on the effects of osseointegration of implants in dental patients. Specifically, the majority of them have been performed in animal experimental models [20][21][22][23][24][27][28][29]31 and only a small number in humans [15][16][17][18] . This literature review aims to research into potential correlations linking the osseointegration process in dental implants to low levels of vitamin D in dental patients.…”
Section: Introductionmentioning
confidence: 99%